PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN MELALUI PERMAINAN HALANG RINTANG “ZONA PETUALANGAN CILIK” DI RA AZRINA MEDAN - Idzni Azhima; Putri Aulia; Homsani Nasution (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Early childhood education aims to maximize the overall development of children aged 0 to 6 years, including their physical motor development. This study focuses on examining the gross motor development of children aged 5 to 6 years at RA Azrina in Medan City through the implementation of the obstacle course activity called “Zona Petualangan Cilik.” A descriptive method with a qualitative approach was used in this research. Based on observations across several aspects of gross motor skills, the following results were obtained: for balance, 60% of children were categorized as Developing as Expected, while 40% were Developing Very Well; for agility, 80% were Developing Very Well and 20% were Beginning to Develop; for strength, 60% were Developing as Expected and 40% were Beginning to Develop; and for coordination, 90% were Developing Very Well and 10% were Beginning to Develop. The findings from both observation and analysis indicate that children aged 5 to 6 at RA Azrina in Medan City are generally showing good progress in gross motor development. Keywords:  Early Childhood, Physical Motor Development, Gross Motor Skills